Interface full-scale reinforced silicon-carbon composite electrode and preparation method and application thereof
The carbon shell is converted into a carbon nanomaterial and connected to the carbon skeleton to form a silicon carbon composite electrode with full-scale strengthening interface, which solves the problem of unstable structure during charging and discharging of the silicon carbon composite electrode and achieves high efficiency The electronic/lithium ion transmission and mechanical mechanical properties are improved, suitable for the application of lithium-ion batteries.
Patent Information
- Application Number
- CN202411527332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing silicon-carbon composite electrodes have unstable structures due to huge volume changes during charging and discharging, low electron/lithium ion transmission efficiency, and poor processing performance, making it difficult to meet the needs of high energy density and long cycle life.
The carbon shell is converted into a carbon shell and is covalently coated with silicon nanomaterials and connected to the carbon frame to form a three-dimensional conductive network with full-scale strengthening interface, achieving stability of the solid-phase electrolyte interface on the surface of the silicon nanomaterial and improving mechanical mechanical properties.
It significantly improves the mechanical stability of the electrode and the electron/lithium ion transmission performance, improves the charge and discharge specific capacity and cycle stability of the lithium-ion battery, and has a simple preparation method, low cost and low energy consumption, which is suitable for large-scale production.
Smart Images

Figure CN119230730A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery electrode preparation, and specifically relates to a silicon-carbon composite electrode and a preparation method and application thereof, and more particularly to a silicon-carbon composite electrode with full-scale interface strengthening and a preparation method thereof and application thereof in lithium ion batteries. Background Art
[0002] With the rapid development of portable electronic devices and electric vehicles, the research on energy storage devices with high energy density, high power density and long cycle life has become the focus of global attention. Among them, lithium-ion batteries have been widely used due to their excellent characteristics in energy density, power density, cycle performance and cost. In order to meet the new requirements of the energy storage market for energy storage devices in terms of energy density, power density and cycle life, the development of new electrode materials has become the key to developing high-performance lithium-ion battery performance.
[0003] Silicon, as a negative electrode active material for lithium-ion batteries that can replace graphite, exhibits higher theoretical specific capacity and excellent rate performance. However, the stress generated by the huge volume change during the charge and discharge process causes the silicon active material to pulverize and collapse, which in turn causes the separation between the active materials and between the active materials and the current collector and the repeated construction of the solid electrolyte interface. Therefore, its capacity decays rapidly and the cycle stability is difficult to meet the needs of practical applications. The nanostructuring of silicon active materials and their composite with carbon nanomaterials are currently effective measures to solve the problem of structural and surface instability caused by the huge volume change during the charge and discharge process, and can significantly improve its charge and discharge cycle performance. In order to avoid the damage of the carbon component and other electrode components caused by the internal stress generated by the volume change of silicon materials during the charge and discharge process, the strategy of introducing an effective space between the silicon component and the carbon component has been widely adopted (Apomegranate-inspired nanoscale design for large-volume-change lithium battery anodes, Nat. Nanotech. 2014, 9, 187;
[0004] Contact-engineered and void-involved silicon / carbon nanohybrids as lithium-ion-battery anodes, Adv. Mater. 2013, 25, 3560–3565). However, this structural design leads to insufficient contact (point-to-point contact or line-to-line contact) between the silicon component and the carbon component in the silicon-carbon composite material, which reduces the efficiency of electron / lithium ion transmission and curbs the improvement of the material's lithium storage performance. In addition, during the electrode processing process, this reserved cavity structure is very easy to break under the action of external stress, affecting the processability of the electrode.
[0005] Therefore, the art hopes to develop a method with simple process, low energy consumption, scalability and low cost to prepare battery electrodes with excellent electron / lithium ion transport properties and the ability to effectively resist internal / external stress changes. Summary of the invention
[0006] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a silicon-carbon composite electrode and its preparation method and application, and in particular to a silicon-carbon composite electrode with full-scale interface strengthening and its preparation method and application in lithium-ion batteries. In the silicon-carbon composite electrode with full-scale interface strengthening of the present invention, the silicon nanomaterial is covalently coated with a carbon shell layer converted by a binder and connected to an interface strengthening carbon skeleton, so as to realize microscopic welding of the interface, which not only stabilizes the solid-phase electrolyte interface layer on the surface of the silicon nanomaterial, but also constructs a three-dimensional multi-level electron / lithium ion transmission network, and also ensures the full-scale (electrode / material / interface) high stability of the electrode structure in terms of mechanical properties and (or) the high efficiency of the electron / lithium ion transmission network during the volume change process of the silicon nanomaterial. The electrode described in the present invention is an ideal negative electrode of a lithium-ion battery, showing excellent mechanical stability and electron / lithium ion transmission performance, and the prepared battery has a high charge and discharge specific capacity, extremely excellent cycle stability and rate performance; moreover, the preparation method of the present invention is simple, low-cost, low-energy consumption, can realize large-scale production, and has broad application prospects.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a silicon-carbon composite electrode with full-scale interface reinforcement, wherein the composite electrode comprises a silicon nanomaterial coated with carbon converted from a binder, and a carbon skeleton reinforced with carbon converted from a binder.
[0009] In the present invention, the silicon nanomaterial is connected (welded) to the interface-strengthened carbon skeleton through a covalently linked binder-converted carbon coating shell. This interface-strengthened connection (welding) includes the following three aspects: ① The carbon converted by the binder realizes the connection (welding) between the interfaces of the carbon skeleton components; ② The silicon nanomaterial is connected (welded) by the binder-converted carbon shell and the carbon skeleton; ③ The carbon shell converted by the binder uniformly coats the silicon nanomaterial and realizes covalent connection (welding) at the interface. The binder-converted carbon shell strengthens the connection of the carbon skeleton components through physical / chemical covalent action, realizes the microscopic welding of the multi-scale interface of the composite electrode, and forms a carbon network with high mechanical stability and conductivity; the binder-converted carbon provides a more stable silicon-carbon composite interface through the covalent coating of the silicon nanomaterial. Therefore, this interface-full-scale-strengthened silicon-carbon composite electrode not only stabilizes the solid electrolyte interface film on the surface of the silicon nanomaterial, but also ensures the high mechanical and (or) electrical stability of the composite material under the action of internal and external pressures.
[0010] Preferably, the silicon nanomaterial may be a silicon nanomaterial of different dimensions, such as silicon nanoparticles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets, etc., preferably including any one of silicon nanoparticles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets or a mixture of at least two thereof, and typical but non-limiting examples of the mixture include: a mixture of nanoparticles and silicon nanowires, a mixture of silicon nanoparticles and silicon nanosheets, a mixture of silicon nanoparticles, silicon nanowires and silicon nanosheets, etc. However, it is not limited to the silicon nanomaterials listed above, and other silicon nanomaterials commonly used in the art may also be used in the present invention.
[0011] Preferably, the binder is petroleum asphalt or its derivatives, or a mixture of any one or at least two of glucose, sucrose, chitosan, starch, citric acid, urea, protein, gelatin, gum arabic, alginate, cellulose, phenolic resin, polyvinylidene fluoride, polyamino acid, polyvinyl pyrrolidone, polycarbonate, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyethyl methacrylate, polyacrylic resin, polyvinyl chloride, polyacrylonitrile, polylactic acid or polystyrene, asphalt and its derivatives. Typical but non-limiting examples of the mixture include: a mixture of glucose and asphalt, A mixture of chitosan and asphalt, a mixture of citric acid and asphalt, a mixture of alginate and asphalt, a mixture of phenolic resin and asphalt, a mixture of polyvinylidene fluoride and asphalt, a mixture of chitosan, urea and asphalt, a mixture of protein, sucrose, phenolic resin and asphalt, a mixture of alginate, polyamino acid, polyvinyl alcohol and asphalt, a mixture of chitosan, phenolic resin, polycarbonate and asphalt, a mixture of gum arabic, polyvinyl pyrrolidone, polyethylene glycol, polymethyl methacrylate, sucrose and asphalt, etc., preferably, the mass percentage of asphalt or its derivatives is not less than 50%.
[0012] Preferably, the carbon skeleton comprises any one of carbon nanotubes, carbon nanowires, carbon fibers, graphene, graphene oxide, reduced graphene oxide, bacterial cellulose-derived carbon fibers or bacterial cellulose-derived carbon fibrils, or a combination of at least two thereof. Typical but non-limiting examples of the mixture include: carbon nanotubes and graphene, carbon fibers and reduced graphene oxide, carbon nanotubes, carbon nanowires and graphene, carbon nanotubes, carbon nanowires, carbon fibers and reduced graphene oxide, etc. Preferably, the mass percentage of graphene-based carbon in the carbon skeleton is not less than 50%.
[0013] Preferably, the weight percentage of silicon nanomaterial in the composite electrode is 30%-99%, for example, 50%, 55%, 57%, 60%, 62.5%, 65%, 66%, 68%, 72%, 75%, 77%, 78%, 80%, 82%, 85%, 87.5%, 90%, 91%, 93%, 95%, 96.5%, 98% or 99%, etc.
[0014] Preferably, the total weight percentage of binder-converted carbon and carbon skeleton in the composite electrode is 1%-70%, for example, 1%, 2%, 3%, 5%, 8%, 10%, 12%, 14%, 16.5%, 18%, 20%, 22%, 25%, 27%, 30%, 35%, 37.5%, 40%, 44%, 47% or 50%, etc.
[0015] In a second aspect, the present invention provides a method for preparing a silicon-carbon composite electrode with full-scale interface strengthening as described in the first aspect, the method comprising the following steps:
[0016] Silicon nanomaterials, carbon nanomaterials and binders are dispersed in water and / or organic solvents to prepare a uniform slurry, a self-supporting composite macrobody is prepared by a physical method, and then dried, and finally subjected to high-temperature heat treatment in a non-oxidizing atmosphere to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement.
[0017] In the present invention, after the mixing step, the binder is wrapped on the surface of the silicon nanomaterial and is evenly dispersed among the carbon nanomaterials.
[0018] In the method of the present invention, after the heat treatment step, the binder is carbonized or denatured, and the converted carbon material realizes full-scale connection (welding) of the composite electrode interface through physical / chemical covalent bonding; the carbon nanomaterial derivative in the carbon skeleton is reduced to a highly conductive carbon nanomaterial.
[0019] Preferably, the solvent includes any one of water, ethanol, ethylene glycol, methanol, propanol, isopropanol, acetone, toluene, carbon tetrachloride, xylene, p-xylene, benzene, cyclohexane, acetonitrile, acetic acid, and ethyl acetate, or a mixture of at least two of them, but is not limited to the solvents listed above. Other commonly used solutions in the art can also be used in the present invention.
[0020] Preferably, the silicon nanomaterial includes any one of silicon nanoparticles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets, or a mixture of at least two of them, but is not limited to the silicon nanomaterials listed above. Other silicon nanomaterials commonly used in the art can also be used in the present invention.
[0021] Preferably, the binder is petroleum asphalt or its derivatives, or a mixture of any one or at least two of glucose, sucrose, chitosan, starch, citric acid, urea, protein, gelatin, gum arabic, alginate, cellulose, phenolic resin, polyvinylidene fluoride, polyamino acid, polyvinyl pyrrolidone, polycarbonate, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyethyl methacrylate, polyacrylic resin, polyvinyl chloride, polyacrylonitrile, polylactic acid or polystyrene.
[0022] Preferably, the carbon skeleton comprises any one or a combination of at least two of carbon nanotubes, carbon nanowires, carbon fibers, graphene, graphene oxide, reduced graphene oxide, bacterial cellulose-derived carbon fibers or bacterial cellulose-derived carbon fibrils, but is not limited to the carbon nanomaterials listed above. Other carbon nanomaterials commonly used in the art can also be used in the present invention.
[0023] Preferably, the solute concentration in the mixed solution is 1wt%-99wt%, for example, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 17wt%, 20wt%, 25wt%, 30wt%, 33wt%, 36wt%, 40wt%, 45wt%, 47.5wt%, 50wt%, 55wt%, 58wt%, 62.5wt%, 65wt%, 68wt%, 70wt%, 73wt%, 77wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92.5wt%, 95wt% or 99wt%, etc., preferably 20wt%.
[0024] In the present invention, the "solute" is a general term for silicon nanomaterials, carbon nanomaterials and binders.
[0025] Preferably, the silicon-carbon composite material macroscopic body is prepared by a physical method using a slurry formed by silicon nanomaterials, carbon nanomaterials and a binder.
[0026] Preferably, the physical method is any one of scraping, spin coating, spraying, dripping, and / or 3D printing, or a combination of at least two thereof.
[0027] Preferably, the drying process is any one of freeze drying, (vacuum) drying or natural air drying, or a combination of at least two of them.
[0028] Preferably, the temperature of the heat treatment is 400°C-1000°C, for example, 400°C, 450°C, 500°C, 600°C, 650°C, 675°C, 700°C, 750°C, 760°C, 780°C, 800°C, 850°C, 880°C, 900°C, 925°C, 950°C, 975°C or 1000°C, etc., preferably 800°C.
[0029] Preferably, the heating rate is 1-20°C / min, for example, 1°C / min, 2°C / min, 5°C / min, 6°C / min, 10°C / min, 15°C / min, 20°C / min, etc., preferably 5°C / min.
[0030] Preferably, the heat treatment time is 0.5-24 h, for example, 0.5 h, 1 h, 2 h, 3 h, 5 h, 7 h, 10 h, 12 h, 13 h, 15 h, 16 h, 18 h, 20 h, 21 h, 22 h, 23 h or 24 h, etc., preferably 2 h.
[0031] Preferably, the non-oxidizing atmosphere is any one of nitrogen, argon, hydrogen, helium or carbon dioxide, or a combination of at least two of them. Typical but non-limiting examples of the combination include: argon atmosphere, argon / hydrogen mixed atmosphere, etc., preferably a mixed atmosphere with a hydrogen volume fraction of 5%.
[0032] As a further preferred technical solution of the method of the present invention, the method comprises the following steps:
[0033] Silicon nanomaterials, carbon nanomaterials and binders are evenly dispersed in water and / or organic solvents by mechanical mixing equipment to obtain a uniform slurry. The mixing time is 10 minutes to 24 hours. A self-supporting composite material macrobody is prepared by a physical method. After drying, the macrobody is heat treated at 400°C to 1000°C in a non-oxidizing atmosphere for 1 hour to 24 hours to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement.
[0034] In a third aspect, the present invention provides a battery negative electrode, which is the three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement as described in the first aspect.
[0035] In a fourth aspect, the present invention provides an electrochemical energy storage device and / or energy storage system, characterized in that the electrochemical energy storage device and / or energy storage system comprises the three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface enhancement as described in the first aspect.
[0036] Preferably, the electrochemical energy storage device and / or energy storage system is a lithium-ion battery, a lithium-sulfur battery, an air battery, etc., preferably a lithium-ion battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention mainly starts from the silicon nanomaterial coupled with a binder, obtains a uniform slurry based on the mechanical mixing of the silicon nanomaterial with the carbon nanomaterial, obtains a self-supporting silicon-carbon composite macroscopic body by a physical method, and further converts the binder into a carbon material by heat treatment to achieve full-scale enhanced connection (welding) of the interface of the silicon-carbon composite electrode, and provides a three-dimensional conductive networked silicon-carbon composite electrode with full-scale enhanced interface and a preparation method thereof. The method has the advantages of a wide range of optional silicon sources, binders and carbon sources, low cost, simple composite material preparation process, low energy consumption, scalability, and compatibility with existing electrode preparation processes.
[0039] (2) The three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement provided by the present invention can be directly applied to lithium-ion battery systems. Since the electrode structure not only inherits the characteristics of silicon nanomaterials themselves (nanoscale is conducive to the transmission of electrons and lithium ions, and the release of stress caused by silicon volume changes), but also realizes full-scale connection (welding) of the electrode interface through physical / chemical covalent action, the mechanical properties of the three-dimensional carbon network and the stability of electron / lithium ion transmission are improved synchronously in all dimensions of electrodes, materials and interfaces, showing extremely excellent charge and discharge specific capacity, cycle stability and rate performance. At a current density of 0.5C, it has a high capacity of 1020-1680mAh g -1 The discharge specific capacity can maintain good cycle performance after more than 100 cycles, and even the capacity retention rate can be as high as 90% after 200 cycles, and the capacity retention rate can still be as high as 81% after 500 cycles, which has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The cross-sectional SEM images of the electrode obtained in Example 1 before and after being compacted at a pressure of 40 MPa;
[0041] Figure 2 The cross-sectional SEM images of the electrode obtained in Comparative Example 1 before and after being compacted at a pressure of 40 MPa;
[0042] Figure 3 Nanoindentation test results of the electrodes of Example 1 and Comparative Example 1;
[0043] Figure 4 The figure is a comparison chart of the hardness and modulus of the electrodes of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0045] Example 1
[0046] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0047] (1) Silicon nanoparticles, graphene oxide and sulfonated petroleum asphalt were mixed in a mass ratio of 8:2:2, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 20 wt %. The slurry was prepared by a doctor blade method combined with vacuum drying to prepare a silicon-carbon composite macro film;
[0048] (2) The silicon-carbon composite macrostructure obtained in step (1) is heat treated at 800° C. in a hydrogen / argon mixed atmosphere for 2 h (heating at 5° C. / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 75 wt%.
[0049] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M LiPF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery had a high capacity of up to 1380 mAh g -1 After 200 cycles, the capacity retention rate can reach 92%, which has extremely excellent cycle stability.
[0050] Example 2
[0051] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0052] (1) Silicon nanoparticles, carbon nanotubes, graphene oxide, glucose and sulfonated petroleum asphalt were mixed in a mass ratio of 6:1:3:1:3, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 80 wt %. The slurry was prepared by a 3D printing method combined with freeze drying to prepare a silicon-carbon composite macroscopic film;
[0053] (2) The silicon-carbon composite macrobody obtained in step (1) is heat treated at 600°C in a hydrogen / argon mixed atmosphere for 0.5 h (heating rate of 10°C / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 61 wt%.
[0054] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M Li PF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the resulting battery had a capacity of up to 1050 mAh g -1 After 200 cycles, the capacity retention rate can reach 96%, which has extremely excellent cycle stability.
[0055] Example 3
[0056] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0057] (1) Silicon nanoparticles, graphene oxide and petroleum asphalt were mixed in a mass ratio of 7:3:1, and N-methylpyrrolidone was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 20 wt %, and the slurry was prepared by a doctor blade method combined with vacuum drying to prepare a silicon-carbon composite macro film;
[0058] (2) The silicon-carbon composite macrobody obtained in step (1) is heat treated at 400° C. in a hydrogen / nitrogen mixed atmosphere for 12 h (temperature increase at 5° C. / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 70 wt%.
[0059] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M Li PF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery has a high capacity of up to 1120 mAh g -1 After 500 cycles, the capacity retention rate can reach 86%, which has extremely excellent cycle stability.
[0060] Example 4
[0061] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0062] (1) Silicon nanoparticles, graphene oxide, polyvinylidene fluoride and sulfonated petroleum asphalt were mixed in a mass ratio of 6:3:1:2, and N-methylpyrrolidone was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 70 wt %. The slurry was prepared by a 3D printing method combined with freeze drying to prepare a silicon-carbon composite macro film;
[0063] (2) The silicon-carbon composite macrobody obtained in step (1) is heat treated at 400° C. in a hydrogen / argon mixed atmosphere for 6 h (temperature increase at 2° C. / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 65 wt%.
[0064] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M Li PF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery has a high capacity of up to 1080 mAh g -1 The weight specific capacity of the battery can reach 88% after 500 cycles, which shows excellent cycle stability.
[0065] Example 5
[0066] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0067] (1) Silicon nanowires, graphene oxide, bacterial cellulose, phenolic resin and sulfonated petroleum asphalt were mixed in a mass ratio of 6:2:2:1:2, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 70 wt %, and the slurry was prepared by a doctor blade method combined with vacuum drying to prepare a silicon-carbon composite macro film;
[0068] (2) The silicon-carbon composite macrobody obtained in step (1) is heat treated at 800°C in a hydrogen / argon mixed atmosphere for 6 h (heating at 15°C / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 56 wt%.
[0069] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M Li PF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery has a high capacity of up to 1011 mAh g -1 After 500 cycles, the capacity retention rate can reach 85%, which has extremely excellent cycle stability.
[0070] Example 6
[0071] In this embodiment, a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement is prepared by the following method, which specifically includes the following steps:
[0072] (1) Silicon nanoparticles, silicon nanowires, graphene oxide and sulfonated petroleum asphalt were mixed in a mass ratio of 6:2:2:2, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 20 wt %. The slurry was used by a doctor blade method combined with vacuum drying to prepare a silicon-carbon composite macro film;
[0073] (2) The silicon-carbon composite macrostructure obtained in step (1) is heat treated at 800° C. in a hydrogen / argon mixed atmosphere for 2 h (temperature increase of 5° C. / min) to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement, wherein the weight percentage of silicon is 76 wt %.
[0074] The composite electrode was used as the test electrode, lithium foil was used as the counter electrode, and the electrolyte was 1M LiPF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery has a high capacity of up to 1510 mAh g -1 The weight specific capacity of the battery can reach 95% after 200 cycles, which shows excellent cycle stability.
[0075] Comparative Example 1
[0076] In this comparative example, silicon nanoparticles and graphene oxide are mixed in a mass ratio of 8:4, and deionized water is used as a solvent to prepare a uniform slurry by mechanical stirring, wherein the solute concentration is 20wt%, and the above slurry is prepared by a scraping method combined with vacuum drying to prepare its silicon-carbon composite macroscopic film. The obtained macroscopic film is heat-treated at 800°C in a hydrogen / argon mixed atmosphere for 2h (temperature increase of 5°C / min), and the silicon nanoparticles in the obtained silicon-carbon composite electrode are accumulated in the skeleton of the physically overlapped graphene, wherein the weight percentage of silicon is 76wt%.
[0077] The above silicon-carbon composite electrode was directly used as the test electrode, the metal lithium foil was used as the counter electrode, and the electrolyte was 1MLiPF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery still had a current density of 980 mAh g -1 The specific capacity is significantly lower than that of the silicon-carbon composite electrode prepared by the present invention; after 200 cycles, the capacity retention rate can reach 55%, and the cycle performance is poor.
[0078] Comparative Example 2
[0079] In this comparative example, silicon nanoparticles, graphene oxide and glucose are mixed in a mass ratio of 8:2:2, and deionized water is used as a solvent to prepare a uniform slurry by mechanical stirring, wherein the solute concentration is 20wt%. The above slurry is prepared by a scraping method and vacuum drying to prepare its silicon-carbon composite macroscopic film. The obtained macroscopic film is heat-treated at 800°C in a hydrogen / argon mixed atmosphere for 2h (temperature increase of 5°C / min). In the obtained silicon-carbon composite electrode, the silicon nanomaterial and the graphene carbon skeleton are physically connected only through the conversion of glucose into carbon, and have a traditional unstable connection interface, wherein the weight percentage of silicon is 77wt%.
[0080] The above silicon-carbon composite electrode was directly used as the test electrode, the metal lithium foil was used as the counter electrode, and the electrolyte was 1MLiPF6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery still had a current density of 1120 mAh g -1 The specific capacity is significantly lower than that of the silicon-carbon composite electrode prepared by the present invention; after 200 cycles, the capacity retention rate can reach 62%, and the cycle performance is poor.
[0081] Comparative Example 3
[0082] In this comparative example, silicon nanoparticles, graphene oxide and sulfonated asphalt were mixed in a mass ratio of 8:2:2, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 20wt%. The slurry was prepared by a scraping method and vacuum drying to prepare its silicon-carbon composite macro film. The obtained macro film was heat treated at 300°C in an argon atmosphere for 2h (5°C / min heating), wherein the weight percentage content of silicon was 72wt%. Since it is difficult to form a stable chemical covalent connection by low-temperature heat treatment, the interface in the obtained silicon-carbon composite electrode is only physically connected by sulfonated asphalt-based carbon.
[0083] The above silicon-carbon composite electrode was directly used as the test electrode, the metal lithium foil was used as the counter electrode, and the electrolyte was 1MLiPF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery still had a current density of 1060 mAh g -1 The specific capacity is significantly lower than that of the silicon-carbon composite electrode prepared by the present invention; after 200 cycles, the capacity retention rate can reach 76%, and the cycle performance is poor.
[0084] Comparative Example 4
[0085] In this comparative example, silicon nanoparticles, graphene oxide and sulfonated asphalt were mixed in a mass ratio of 8:2:2, and deionized water was used as a solvent. A uniform slurry was prepared by mechanical stirring, wherein the solute concentration was 20wt%. The slurry was prepared by a doctor blade method and vacuum drying to prepare its silicon-carbon composite macro film. The obtained macro film was heat treated at 1100°C in a hydrogen / argon mixed atmosphere for 2h (5°C / min heating), wherein the weight percentage content of silicon was 75wt%. Since the binder was completely converted into carbon and was brittle after this high temperature treatment, the physical connection performance was reduced, resulting in poor mechanical properties of the composite macro film, which was easily crushed and fell off from the substrate.
[0086] The above silicon-carbon composite electrode was directly used as the test electrode, the metal lithium foil was used as the counter electrode, and the electrolyte was 1MLiPF 6 / EC:DEC (1:1; v / v), i.e., a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate, and a Celgard 2400 separator, were assembled into a button-type lithium-ion battery in a glove box with oxygen and water contents less than 1 ppm. At a current density of 0.5 C, the obtained battery still had a current density of 1210 mAh g -1 The specific capacity is significantly lower than that of the silicon-carbon composite electrode prepared by the present invention; after 200 cycles, the capacity retention rate can reach 57%, and the cycle performance is poor.
Claims
1. A silicon-carbon composite electrode with full-scale interface strengthening, characterized in that: The composite electrode includes a silicon nanomaterial coated with carbon converted from a binder, and a carbon skeleton reinforced with carbon converted from a binder; The carbon skeleton and the carbon-coated silicon nanocomposite material are connected (welded) by converting carbon into a binder; the binder-converted carbon strengthens the mechanical properties and (or) electrical stability of the interface between the carbon skeleton unit and the silicon nanomaterial and the carbon skeleton unit through physical / chemical covalent action; In the composite electrode, the weight percentage of silicon nanomaterial is 30%-99%; In the composite electrode, the total weight percentage of the binder converted carbon and the carbon skeleton is 1%-70%.
2. The composite electrode according to claim 1, characterized in that The silicon nanomaterial includes any one of silicon nanoparticles, silicon nanowires, silicon nanotubes or silicon nanosheets, or a mixture of at least two of them.
3. The composite electrode according to claim 1, characterized in that The binder is petroleum asphalt or its derivatives, or a mixture of any one or at least two of glucose, sucrose, chitosan, starch, citric acid, urea, protein, gelatin, gum arabic, alginate, cellulose, phenolic resin, polyvinylidene fluoride, polyamino acid, polyvinyl pyrrolidone, polycarbonate, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyethyl methacrylate, polyacrylic resin, polyvinyl chloride, polyacrylonitrile, polylactic acid or polystyrene.
4. The composite electrode according to claim 1, characterized in that: The carbon skeleton comprises any one of carbon nanotubes, carbon nanowires, carbon fibers, graphene, graphene oxide, reduced graphene oxide, carbon fibers derived from bacterial cellulose, or carbon fibers derived from bacterial cellulose, or a combination of at least two thereof.
5. The method for preparing a composite electrode according to claim 1, characterized in that: The method comprises the following steps: Silicon nanomaterials, carbon nanomaterials and binders are dispersed in water and / or organic solvents to prepare a uniform slurry, a self-supporting composite macrobody is prepared by a physical method, and then dried, and finally subjected to high-temperature heat treatment in a non-oxidizing atmosphere to obtain a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement.
6. The method according to claim 5, characterized in that The solvent includes any one of water, ethanol, ethylene glycol, methanol, propanol, isopropanol, acetone, toluene, carbon tetrachloride, xylene, p-xylene, benzene, cyclohexane, acetonitrile, acetic acid, and ethyl acetate, or a mixture of at least two thereof; The silicon nanomaterial includes any one of silicon nanoparticles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets, or a mixture of at least two of them; The binder is petroleum asphalt or its derivatives, or any one or a mixture of at least two of glucose, sucrose, chitosan, starch, citric acid, urea, protein, gelatin, gum arabic, alginate, cellulose, phenolic resin, polyvinylidene fluoride, polyamino acid, polyvinyl pyrrolidone, polycarbonate, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyethyl methacrylate, polyacrylic resin, polyvinyl chloride, polyacrylonitrile, polylactic acid or polystyrene; The carbon skeleton comprises any one or a combination of at least two of carbon nanotubes, carbon nanowires, carbon fibers, graphene, graphene oxide, reduced graphene oxide, carbon fibers derived from bacterial cellulose, or carbon fibers derived from bacterial cellulose; The mass percentage of the solute in the mixed solution is 1%-99%.
7. The method according to claim 5, characterized in that The physical method is any one of scraping, spin coating, spraying, dripping, and / or 3D printing, or a combination of at least two thereof; The drying process is any one of freeze drying, (vacuum) drying or natural air drying, or a combination of at least two of them; The heat treatment temperature is 400°C-1000°C, the heating rate is 1-20°C / min, and the heat treatment time is 0.5-24h; The non-oxidizing atmosphere is any one of nitrogen, argon, hydrogen, helium or carbon dioxide, or a combination of at least two of them.
8. A battery negative electrode, characterized in that: The negative electrode is a three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement as described in claim 1.
9. An electrochemical energy storage device and / or energy storage system, characterized in that: The electrochemical energy storage device and / or energy storage system comprises the three-dimensional conductive networked silicon-carbon composite electrode with full-scale interface reinforcement as described in claim 1.
Citation Information
Cited By
Lithium ion battery silicon-carbon composite negative electrode material and preparation method and application thereof
CN119812271A